Antecedents And Outcomes of Online Social Networks (OSN) Usage among Public Sector Employees - Almarri, Hamad; Ameen, Ali; Isaac, Osama; Khalifa, Gamal S. A.; Bhaumik, Amiya (International Journal of Psychosocial Rehabilitation, 2020)
The new technologies are enabling organizations to be flatter, networked, and more flexible. Organizations in the 21st century inevitably make substantial investments in Information Technology (IT) in order to achieve competitive advantage, by spending enormous sums of money on computer hardware, software, communication networks, databases and specialized personnel. Consequently, Information Technology is not exclusive to the workplace but has also become widespread in public areas and houses. The main objective of this study is to determine factors influencing the adoption and impact of online social networks use in terms of performance among employees within Tourism Development and Investment Company (TDIC) in Abu Dhabi. This study collected data through quota nonprobability sampling, and 401 valid responses were received. Structural Equation Modelling- Variance based (SEM-VB) through partial least squares (PLS) method to analyse the research model using the software of SmartPLS 3.0. Although various limitations exist, the findings have been encouraging, as it has managed to shed some lights on new variables affecting the use of online social networks. This study proposed an extended model of the Unified Theory of Acceptance & use of Technology (UTAUT) and found that three variables play an important role to determine the performance impact of online social networks namely performance expectancy, effort expectancy, and actual usage. The findings of this study can provide policymakers with important insights on how to more successfully incorporate online social networks to improve performance and the services of public sector, and how to encourage top managers to ensure that employees are more likely to utilize new technologies and thereby enabling better work outcome, wider reach of services, gives employees more control over their daily tasks and enhances their performance.